When Earth Matters: Bessie Head’s When Rain Clouds Gather - Bayer Gerd (Open Cultural Studies, 2019)
This essay discusses Bessie Head’s When Rain Clouds Gather from an ecocritical perspective, asking how her late 1960s’ novel already anticipated some of the politics of early twenty-first-century environmental thinking in the postcolonial sphere. The alliance of various marginalized characters who, one way or another, violate against existing hegemonic structures replaces the ideological and cultural conflict over territory, which derived directly from the colonialist past, with an agricultural revolution that aims to empower those who most closely resemble the subaltern classes variously theorized in postcolonial theory. This re-turn to the physical or even Real, to the materiality of the earth, opens up an alternative to the cultural essentialism that, from its beginning, created numerous stumbling stones on the path towards decolonization. Through its turn towards farming and the land and away from cultural forms of hegemony, the novel emphasizes the materiality of reality.